Community Empowerment dalam Meningkatkan Kapasitas Tata Kelola Pemerintahan Desa Ketapanrame sebagai Desa Wisata - Novyasari Maharani, Dinda; Asmorowati, Sulikah (Jurnal Ilmiah Administrasi Publik, 2024)
Governance capacity in village government can be developed using the concept of governance performance by implementing Community Empowerment. The Ketapanrame Village Government makes community empowerment one of the keys to the success of creating a tourist village that is able to provide achievements for the village at national level. This research aims to analyze the governance of  Ketapanrame Village Government by involving community in developing tourist village using a descriptive qualitative approach and an interpretative-political perspective. Analysis and interpretation of data shows that development of the Tourism Village in Ketapanrame is able to empower the community in tourism operational activities. This was carried out by BUMDes Mutiara Welirang which formed two community groups, namely the Taman Ghanjaran Joint Business Group (KUB) and the Rakasiwi Tourism Awareness Group (Pokdarwis). These empowerment efforts have resulted in economic and welfare improvements as well as opening up job opportunities for people of Ketapanrame Tourism Village. Community Empowerment or community empowerment is very necessary to develop governance capacity at village level through developing potential of human resources.